Suitable Conditions for Detecting Apple Chlorotic Leaf-Spot Virus in Apricot Trees by Enzyme-Linked Immunosorbent-Assay (Elisa) - Llácer, Gerardo; Cambra, Mariano; Lavina, A.; Aramburu, Jose (2017)
Apple chlorotic leaf spot virus (CLSV) occurs irregularly within infected apricot trees and this causes difficulties in detecting it. This work aimed at studying the most adequate sampling time and suitable parts of the plant for a reliable detection of CLSV in apricot, using the enzyme-linked immunosorbent assay (ELISA) technique. Detection was most reliable on fruits, in spring, any time during their development. The results obtained with this method provided some evidence against the claimed association between CLSV and "viruela" disease (apricot pox).